Learning Community In Argumentative Writing Using Audio Visual Through Lesson (The First Year Of MA Al-Muslim Islamic Boarding School): Learning Community In Argumentative Writing Using Audio Visual Through Lesson (The First Year Of MA Al-Muslim Islamic Boarding School) - Nurul Izzah; Misnar (Department of English Education, Faculty of Teacher Training and Education, Almuslim University, 2022)
In learning English at school, argumentative writing is one of the materials that are considered difficult for students to understand. In general, the learning model developed by English teachers is in conventional learning activities. Therefore, it is necessary to apply the learning of Argumentative Writing Using Audio Visual Through Lesson Study (The First Year of MA Al-Muslim Islamic Boarding School). One of the types of lessons considered by researchers can motivate students to play an active and fun role in the teaching and learning process. This type of classroom action research is carried out through 4 stages, namely: planning, implementing actions, observing and reflecting. The data collected in this study were the students' scores in working on the questions given the initial and final tests, the results of observations on the learning steps and the results of interviews regarding students' understanding and difficulties. The results of this study can be concluded that students' learning mastery also experienced an increase, in the first cycle by 75% and becoming 85% in the second cycle. The increase in student learning outcomes was also followed by an increase in student learning activities by 83.64% in the first cycle and increased to 89.88% in the second cycle. This shows that learning argumentative writing through lesson study can improve student learning outcomes.